Seabather's eruption: report of five cases in southeast region of Brazil - HADDAD JUNIOR, Vidal (2001)
The authors report five cases of seabather's eruption, a typical dermatitis associated predominantly to the jellyfish Linuche unguiculata (Cnidaria), that causes erythematous and pruriginous papules on areas of the skin of bathers covered by swimsuits. The rash is characteristic and the eruption is commom in the Caribbean, Florida, Mexico and Gulf States of USA. The cases are the first reported in Brazil and larvae of the jellyfish are present in the waters where the accidents happened.